Biosafety Training and Introduction to Livestock Diseases Using Participatory Rural Appraisal Method in Pade Angen Livestock Group East Lombok Regency - Kholik, Kholik; Pradana, Munawer; Haddar, Mariyam Al; Nofisulastri, Nofisulastri; Riwu, Katty Hendriana Priscillia; Dharmawibawa, Iwan Doddy; Sukri, Akhmad (Jurnal Pengabdian UNDIKMA, 2024)
The community service aims to introduce the application of biosafety and biosecurity and provide the ability to recognize livestock diseases simply with the participatory rural appraisal (PRA) method in reducing the transmission of livestock diseases in East Lombok Regency. The implementation methods of the activities include a survey of the service location to identify problems, socialization of the program activity to the target community, education about biosecurity and biosafety, and an introduction to simple livestock disease detection based on community participation with PRA, then continued with training on applying simple biosecurity and biosafety and simple livestock disease detection methods with PRA proportional piling and matrix scoring methods. The data of PRA proportional piling and matrix scoring based on disease symptom data will be mapped and ranked using descriptive analysis. The results of this community service were obtained from members of The Pade Angen II Livestock Group could use personal protective equipment (PPE) correctly by 80%. The detection of disease based on symptoms using the proportional piling and matrix scoring methods obtained repeat breeding events with symptoms of repeated mating of 21%, helminthiasis with symptoms of worms of 14%, itching of 4%, diarrhea of 4%, and scabies with symptoms of itching of 8%. Foot and mouth disease was also still found with symptoms of wounds on the feet and salivation of 11%, miscarriage of 4% and fever of 1%, coccidiosis with symptoms of bloody diarrhea of 10%, colibacillosis with symptoms of diarrhea of 6%, bloat with symptoms of bloating of 3% and fever of 1%.